Age and gender related changes on total antioxidant/oxidant status and electrolyte composition of saliva - Erdal Ergünol; Rabia Şemsi; Aylin Sepici Dinçel (Aspects of Molecular Medicine)
Background: Saliva is used as an important biological material in the diagnosis and treatment of various diseases to collect easily, to be cheap, to have a minimal risk of infection. Here in that study we aimed to evaluate age and gender-related changes on total antioxidant/oxidant status and electrolyte composition of saliva levels in individuals. Methods: A total of 30 young adult (21.2 ± 2.47 years) and 14 adult (51.6 ± 9.35 years) subjects were included in the study. Stimulated saliva samples were collected. Cortisol, amylase, oxidative stress biomarkers (total antioxidant status and total oxidant status) were measured by ELISA and spectrophotometric manual methods and electrolyte level of saliva samples were determined by autoanalyzer. Results: Salivary concentrations of biomarkers of young adults were compared to adult subjects, there was a statistically significant difference between cortisol (μg/dL) (p = 0.003), Ca+2(mg/dL) (p = 0.004), TAS (mmol Trolox Equiv/L) (p = 0.001), BUN (mg/dL) (p = 0.02), Mg+2 (mg/dL) (p = 0.02), and K+ (mmol/L) (p = 0.05) levels, but there was no significant difference was found between uric acid (mg/dL) (p = 0.44), Cl- (mmol/L) (p = 0.07), amylase (ng/mL) (p = 0.47), phosphate (mg/dL) (p = 0.63), Na+(mmol/L)(p = 0.21), and TOS (μmol H2O2 Equiv/L) (p = 0.70) levels. We evaluated salivary cortisol, amylase, and electrolyte levels of groups that we commented on their relationship between oxidant-antioxidant defense systems of the saliva and their correlations with age and gender. Conclusions: This study could suggest the use of saliva samples to correlate with age and representing the levels of the most common biological parameters for routine use and antioxidant-oxidant enzymes for clinical trials.